PENDAMPINGAN RECOVERY BISNIS MELALUI INOVASI PRODUKSI DAN ADOPSI PLATFORM DIGITAL PADA USAHA IKAN AIR TAWAR DI DESA SIDOMEKAR KECAMATAN SEMBORO KABUPATEN JEMBER - Destari, Fajar; Faiqotul, Irliana; Hasan, Fuad (Ekalaya: Jurnal Pengabdian Kepada Masyarakat Indonesia, 2022)
In the midst of the Covid 19 pandemic, many SMEs experienced a decline in their turnover due to business traffic and many economic activities being locked down, this had an impact on their income level. From the results of visits and interviews conducted with service partners, information was obtained from BERKAH KU freshwater fish farming, this business was founded in 2007 and has been running for 13 years within a period of 13 years. production and the existence of technology, and these things are very threatening to the existence and activities as well as cross-economy first during the COVID 19 pandemic. The minimal types of processed products include, among others, the selection of marketing communication media that are still active, the lack of knowledge of business actors about e-commerce platform. The existence of the Covid 19 pandemic is an unavoidable threat for all business actors not to do business for freshwater fish entrepreneurs because all businesses experienced a decline in turnover of almost 80%. Based on the results of research-based service that has been carried out, it can be said that the programs that have been planned and discussed will help improve marketing through the use of technology and product innovation. The first activity is program socialization in increasing knowledge about technology in marketing products. The second activity is to give demonstrations to partners by cheff in innovating products from raw fish raw materials into processed frozen food products